2021
DOI: 10.21608/asdj.2022.121423.1108
|View full text |Cite
|
Sign up to set email alerts
|

Title: Cleaning ability and Apically Extruded Debris of Three Single file Rotary Nickel Titanium systems (an in vitro study)

Abstract: Background:The aim of this study was to evaluate three single rotary NiTi systems regarding their cleaning ability and the amount apically extruded debris. Methodology: A total of forty five extracted permanent mature lower anteriors were divided then instrumented in three groups (n = 15): Fanta AF F One file, OneShape file and OneCurve file. 2.5% Sodium hypochlorite was used as an irrigant. preweighets and postweights were recorded for apical extrusion. Teeth were longitudinally splited into two halves. Image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Previous research has compared the first launched AF F One single‐file NiTi rotary system (size 25, 0.06 taper; Fanta Dental Material Co.) that is made of a proprietary AF‐R wire technology to various rotary and reciprocating systems. These studies showed that AF F One instruments had lower cyclic fatigue resistance than 2Shape instrument after clinical usage (Ubaed & Bakr, 2022), produced more debris but better cleaning ability than One Shape and OneCurve systems (Mogahed et al, 2021), had better shaping ability than a prototype instrument in simulated canals (Di Nardo et al, 2020), were less effective than certain reciprocating systems in removing calcium silicate‐based sealer (Madarati et al, 2023) and in eliminating Enterococcus faecalis biofilm from infected root canals (Hamed et al, 2022), but showed improved resistance to flexural fatigue compared with a prototype instrument (Gambarini et al, 2019). These preliminary findings indicate that using flat design instruments instead of other market‐available options may not offer the advantages claimed by manufacturers, and further research is necessary to assess their mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has compared the first launched AF F One single‐file NiTi rotary system (size 25, 0.06 taper; Fanta Dental Material Co.) that is made of a proprietary AF‐R wire technology to various rotary and reciprocating systems. These studies showed that AF F One instruments had lower cyclic fatigue resistance than 2Shape instrument after clinical usage (Ubaed & Bakr, 2022), produced more debris but better cleaning ability than One Shape and OneCurve systems (Mogahed et al, 2021), had better shaping ability than a prototype instrument in simulated canals (Di Nardo et al, 2020), were less effective than certain reciprocating systems in removing calcium silicate‐based sealer (Madarati et al, 2023) and in eliminating Enterococcus faecalis biofilm from infected root canals (Hamed et al, 2022), but showed improved resistance to flexural fatigue compared with a prototype instrument (Gambarini et al, 2019). These preliminary findings indicate that using flat design instruments instead of other market‐available options may not offer the advantages claimed by manufacturers, and further research is necessary to assess their mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have reported conflicting results regarding the performance of flat-side instruments. For instance, Ubaed and Bakr (2022) found that AF F-One exhibited lower cyclic fatigue resistance compared to 2Shape instruments after clinical usage, whilst Mogahed et al (2021) observed that AF F-One generated more debris but demonstrated superior cleaning ability compared to One Shape and OneCurve systems. Conversely, Di Nardo et al (2020) reported better shaping ability of flat-side instruments, and Gambarini et al (2019) demonstrated improved resistance to flexural fatigue in comparison to nonflat-side prototype counterparts.…”
Section: Introductionmentioning
confidence: 99%